Development of Science Literacy-Oriented Interactive Learning Multimedia on Nanotechnology Applications: NanoQuest - Aghnina Farhah; Cucu Zenab Subarkah; Citra Deliana Dewi Sundari (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
This study aimed to develop, validate, and assess the feasibility of an Android-based interactive learning multimedia named NanoQuest, which is oriented toward science literacy in the topic of nanotechnology applications. The study employed the Design-Based Research (DBR) method and the ADDIE approach, implemented up to the development stage. The product was validated by subject matter and media experts and tested on chemistry education students. Data were obtained from validations by three expert validators and a feasibility test involving 15 chemistry education students. The validation results showed that all aspects received an average r score of 0.87, indicating a high level of validity. The feasibility test yielded an average score of 87.55%, categorized as “feasible.” NanoQuest consists of four subtopics and five contextual essay questions designed to develop science literacy components: content, process, context, and attitude. The findings indicate that NanoQuest is valid, feasible, and supports the enhancement of students’ science literacy.